Down syndrome associated with father's age in Norway. - Erickson, J D (1981)
Records of births in Norway in 1967 to 1978 were examined for evidence of an increased risk of Down syndrome associated with older paternal age. From among some 685 000 total births with known maternal and paternal age, 693 cases of Down syndrome were reported to the Medical Birth Registry of Norway. The effect of paternal age was assessed by classifying fathers as young and old on the basis of several definitions. The effect of maternal age was removed by stratifying the data on single years of mothers' age. When fathers were considered young if they were less than or equal to 49 and old if they were less than or equal to 50, the analysis yielded a statistic for the test of a one-sided hypothesis which was significant at the 0.05 level. There appears to be an increase risk (perhaps 20 to 30%) of Down syndrome associated with older fathers, independent of maternal age effect. If this increase does in fact exist, it is much smaller than the increases in risk associated with advancing maternal age, and because older men contribute a relatively small proportion of total births their contribution to the communal burden of Down syndrome is quite small. However, the finding is of aetiological interest and is the first indication of a significant paternal age effect where control for maternal age has been stringent.